Development and application of irreversible thermochromic paints - Kitagawa, Akiharu (2022)
Rolls-Royce develops and manufactures some of the most efficient turbine jet engines in the world using their cutting-edge technologies and research. Over the years, the company has improved their engines by increasing the fuel conversion efficiency, reducing the environmental and health impacts, and introducing new materials for the engine parts. In such engine developments, temperature is one of the most important parameters to optimise the performance efficiency of the engine and ensure the lifetime of the engine components. The temperature of the hottest region of the latest engines can reach from 1400 to 1700 °C, which could be a deteriorating condition for the engine parts. To ensure the lifetime of the engine parts whilst increasing the operation temperature, various techniques have been developed to protect the parts and obtain temperature information from the engine tests.